Specificity and Affinity of Sialic Acid Binding by the Rhesus Rotavirus VP8* Core - Dormitzer, Philip R. (American Society for Microbiology, 2002)
Nuclear magnetic resonance spectroscopy demonstrates that the rhesus rotavirus hemagglutinin specifically binds α-anomeric N-acetylneuraminic acid with a K(d) of 1.2 mM. The hemagglutinin requires no additional carbohydrate moieties for binding, does not distinguish 3′ from 6′ sialyllactose, and has approximately tenfold lower affinity for N-glycolylneuraminic than for N-acetylneuraminic acid. The broad specificity and low affinity of sialic acid binding by the rotavirus hemagglutinin are consistent with this interaction mediating initial cell attachment prior to the interactions that determine host range and cell type specificity.